Abundance of Gastropods in The Estuary Area of Liku Village, Samaturu District, Kolaka Regency - Ade Israwati (Journal of Biological Science and Education, 2021)
Gastropods have an important role in the aquatic food chain. The purpose of this study was to determine the abundance of Gastropod species in the area around the estuary of Liku Village, Samaturu District, Kolaka Regency. This research was conducted in Liku Village, Samaturu District, Kolaka Regency. The research variable consists of the independent variable (X) in the form of the calculation of gastropod abundance and the dependent variable (Y), namely the estuary area of Liku Village, Samaturu District, Kolaka Regency. The method used in this practicum is the plot placement method with the design of using observation stations for 3 repetitions in which 5 plots of observation sampling are made in each station, so that in total there are 15 data collection times. The data analysis technique used is descriptive technique. The abundance calculation results showed that the abundance of 2 species Telescopium telescope and the Littorina scabra species. Keywords: Estuary, abundance, Gastropods.